ANALYSIS OF FACTORS AFFECTING WORK-RELATED STRESS AMONG STUDENTS IN THE INDUSTRIAL SECTOR - Inez Sri Wahyuningsi Manguling (Universitas Negeri Makassar, 2026)
This study aims to analyze the factors influencing job stress among students during industrial internship programs. A literature review approach was employed, drawing on 23 national and international journal articles published between 2020 and 2025, covering contexts of vocational college students, professional education, and vocational high school trainees. The findings reveal that internship-related job stress is multidimensional, influenced by four major categories: individual factors (self-efficacy, achievement motivation, mental readiness, and psychological capital), job-related factors (work overload, long working hours, and effort–reward imbalance), social factors (support from peers, supervisors, and family), and organizational factors (work systems, internship policies, and supervision quality). These factors interact dynamically to determine stress levels and students’ adaptability within industrial environments. The study emphasizes the importance of social support and effective mentoring systems in mitigating job stress and enhancing work readiness. The findings are expected to serve as a reference for educational institutions and industries in designing internship programs that are more adaptive to students’ psychological well-being.